Empowerment of Women in the Rattan and Ketak Handicraft Industry in Lombok - Bahya Aliftri (Journal of Economic Perspectives and Business Innovation, 2025)
AbstractThe empowerment of women in the rattan and ketak handicraft industry plays an important role in strengthening household economies and preserving local cultural heritage in Lombok. This study explores the forms of women’s participation, the impact of empowerment programs, and the challenges faced in developing the handicraft sector. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving women artisans and local stakeholders. The findings show that women’s involvement in production, design innovation, and marketing contributes significantly to family income and community economic resilience. Training programs, access to microfinance, and cooperative networks enhance skills and entrepreneurial capacity. However, limitations in market access, technology adoption, and product standardization remain obstacles to growth. The study concludes that sustainable empowerment strategies, supported by government and community partnerships, are essential to improve women’s welfare and the competitiveness of Lombok’s handicraft industry. Keywords: women empowerment, handicraft industry, rattan and ketak, local economy, Lombok